РЕЗУЛЬТАТЫ ПРОГРАММЫ ВНЕДРЕНИЯ СТРАХОВАНИЯ СЕЛЬСКОГО ХОЗЯЙСТВА И ВОЗМОЖНОСТИ РАЗВИТИЯ В РЕСПУБЛИКЕ АРМЕНИЯ - Panosyan , I. (EurasianUnionScientists, 2021)
In order to reduce climate risks and ensure sustainable development of agriculture, the agricultural insurance system has been introduced and effectively operates in different countries of the world. In 2019, the Government of the Republic of Armenia approved a program for the introduction of agricultural insurance. The article analyzes in detail the results of the pilot program of agricultural insurance in the Republic of Armenia, according to the issues of crops, risks, damage assessment, compensation, as well as the development of agro-culture, outlines the steps to be taken for the further development of the system.